Performance of Sustainable Underwater Concrete Containing GGBS and Micro Silica with Anti-Washout - Amer Salih, Moslih; Kamil Ahmed, Shamil; Salih Mohammed, Ahmed (Civil Engineering Journal, 2025)
Anti-washout concrete (AWC) is engineered for underwater constructions, with resistance to dispersion achieved through the use of anti-washout admixtures (AWAs). This study experimentally investigated the design of sustainable anti-washout concrete mixtures containing a high content of by-product waste materials. The study aims to evaluate sustainable underwater concrete mixtures with high supplementary cementitious materials content, analyze the influence of AWA on compressive strength, and assess the compatibility of anti-washout admixture with both SCMs and superplasticizers. However, the interaction of AWA with a high content of ground granulated blast furnace slag (GGBS) and microsilica in underwater concrete has not been previously investigated. Two groups of concrete mixtures were developed: the first group consisted of two sustainable mixtures, with and without AWA, containing 52.15% ordinary Portland cement (OPC), 43.5% GGBS, and 4.35% micro silica. The second group consisted of two conventional mixtures: one with 100% OPC and the other with 100% OPC plus AWA. Fresh properties, such as slump flow, viscosity (measured by the V-funnel), and air content, were evaluated. Compressive strength was measured to assess mechanical performance. Durability was investigated using four tests: rapid chloride penetration tests (RCPT), water penetration, water absorption, and initial surface absorption tests (ISAT). An anti-washout test was conducted to determine the effectiveness of AWC in minimizing the washout of cement particles. The mixture design introduces an innovative approach to utilizing high levels of SCMs for producing high-strength, durable, and sustainable AWC. The durability results showed that the ISAT test was ineffective for evaluating concrete performance underwater. This research contributes to understanding the effects of AWAs and their compatibility with superplasticizers and SCMs. AWA forms a thixotropic gel that protects cement particles from washout and is highly compatible with superplasticizers.